Climate changes influence in occupational exposure to fungi and mycotoxins - Viegas, Carla (2016)
Climate changes and their effects on fungal distribution and activity are aspects of concern regarding the human exposure to mycotoxins. An exhaustive search was made for papers available in scientific databases reposrting the influence that climate cchange has on fungi and mycotoxins. Also a review regarding fungal burden, collected between 2010 and 2015 in different settings, was done to support the discussion about future fungi and mycotoxins ocuupational exposure. A. flavus complex, E. graminerarum complex and F. verticilliodes were the most reported to be influenced by climate changes. We noted also that the analyzed Portuguese settings presented already an occupational problem due to their fungal burden. It will be important to know future climate changes to select what complexes/species and strains, and consequently the mycotoxins, we should consider as indicators of an occupational problem. In addition, epidemiologic studies are needed to increase knowledge about potential health effects related with the exposure to both risk factors.